2015
DOI: 10.1186/s13014-015-0454-0
|View full text |Cite
|
Sign up to set email alerts
|

Can dosimetric parameters predict acute hematologic toxicity in rectal cancer patients treated with intensity-modulated pelvic radiotherapy?

Abstract: BackgroundTo identify dosimetric parameters associated with acute hematologic toxicity (HT) in rectal cancer patients undergoing concurrent chemotherapy and intensity-modulated pelvic radiotherapy.MethodsNinety-three rectal cancer patients receiving concurrent capecitabine and pelvic intensity-modulated radiation therapy (IMRT) were analyzed. Pelvic bone marrow (PBM) was contoured for each patient and divided into three subsites: lumbosacral spine (LSS), ilium, and lower pelvis (LP). The volume of each site re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Approximately half (40-50%) of bone marrow is localized in pelvic region [47,48]. Majority of available clinical data describes the application of intensity modulated radiation therapy (IMRT) for BMS-RT for prostate, cervical, rectum, anal cancers [47,[49][50][51][52][53][54][55][56][57][58]. In macroscopic cervical and rectum cancer dynamic irradiation techniques are still not first-line treatment options due to concerns over internal organ motion [8,9,59].…”
Section: Bone Marrow Sparing Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately half (40-50%) of bone marrow is localized in pelvic region [47,48]. Majority of available clinical data describes the application of intensity modulated radiation therapy (IMRT) for BMS-RT for prostate, cervical, rectum, anal cancers [47,[49][50][51][52][53][54][55][56][57][58]. In macroscopic cervical and rectum cancer dynamic irradiation techniques are still not first-line treatment options due to concerns over internal organ motion [8,9,59].…”
Section: Bone Marrow Sparing Rtmentioning
confidence: 99%
“…In CRT for rectal cancer Yang et al showed that patients with coxal (bilateral ilium, ischium and pubic) BM-V45 and sacral BM-V45 experienced lower WBC and ANC nadirs [53]. In another paper, Wan et al indicated that lumbosacral BM-V40 predicted grade ≤ 2 HT in CRT for rectal cancer [54]. In the study including 100 women, Chang et al noted that IMRT was superior to 3-D RT in medium and high doses (BM-V20, BM-V30, BM-V40) and mean BM dose [55].…”
Section: Total Bone Marrow Sparing Rt In Treatment Areamentioning
confidence: 99%
“…Hence, selective sparing of pelvic osseous structures may be a viable option to decrease HT during concomitant CH-RT in anal cancer patients [9]. In several studies, a significant correlation between different dose-volume metrics and blood cell nadirs and/or HT was found [10][11][12][13][14][15]. Other than anal cancer, different clinical contexts were investigated such as cervical, rectal, lung and prostate cancer.…”
Section: Introductionmentioning
confidence: 98%
“…In 50 patients treated with IMRT, a higher V20 of the pelvic bone marrow was associated with lower white blood cell nadir ( p = 0.048) and patients with V40 ≥ 41% of the lumbo-sacral bone marrow had higher risk to develop ≥Grade 3 hematologic toxicity [ 26 ]. The most comparable study design was from Wan et al [ 27 ]. Here the V40 of the lumbosacral spine was associated with clinically significant grade ≥ 2 hematologic toxicity in patients receiving conventional concurrent CRT (50 à 2 Gy, IMRT, Capecitabine) (grade ≥ 2hematologic toxicity with V40 ≥ 60% vs. V40 < 60% was 38.3% vs.13%, p = 0.005).…”
Section: Discussionmentioning
confidence: 99%